Warm water infusion colonoscopy: a review and meta-analysis - Rabenstein, T.; Radaelli, F.; Zolk, O. (Endoscopy, 2012)
Background and study aims: Warm water infusion instead of traditional air insufflation during the insertion phase of colonoscopy has been proposed to reduce pain and improve patient acceptance of the procedure. This systematic review aimed to compare warm water infusion with standard air insufflation according to findings from randomized controlled trials (RCTs). Methods: In a systematic review and meta-analysis of RCTs comparing warm water infusion with standard air insufflation, primary outcome measures were procedure-related (cecal intubation, time to cecal intubation, and adenoma detection rates) and patient-related (pain).Results: Nine studies (1283 patients) were included. Warm water infusion, as sole modality for facilitating insertion, was associated with a fourfold higher risk of cecal intubation failure compared with air insufflation (risk ratio [RR] 4.01, confidence interval [CI] 1.17 to 13.78, P = 0.03), but this risk did not significantly differ between warm water infusion and air insufflation with the hybrid technique (i. e., brief use of air when difficulty, e. g. poor view, was encountered). Warm water infusion and air insufflation were associated with similar cecal intubation times (P = 0.62) and adenoma detection rates (P = 0.49), but with warm water infusion patients experienced significantly less pain (P < 0.00001) and a significantly lower proportion requested sedation and/or analgesia (RR 0.48, CI 0.35 to 0.66, P < 0.00001). Conclusions: Although failure of cecal intubation is more frequent with warm water infusion, technical modifications, i. e., short air insufflations, can abolish this. Warm water infusion is less painful than standard air insufflation, reduces the need for sedation/analgesia, and improves patient acceptance of colonoscopy, without additional adverse reactions.